The Integration of Social Studies Learning in the Project of Strengthening the Profile of Pancasila Students in Driving School - Fitria Martanti; Joko Widodo; Rusdarti Rusdarti; Agustinus Sugeng Priyanto (International Conference on Science, Education, and Technology, 2023)
Character is an important thing that must be demonstrated in the learning process. Characters that are embodied in learning must be adapted to the curriculum used. The profile of Pancasila Student is an expected character to be demonstrated in the implementation of Merdeka Curriculum. This study aims to look at the implementation of project-based learning in driving schools, especially in the integration of social studies material that can be carried out in driving schools. In addition, it also aims to look at the driving and inhibiting factors in integrating social studies material into project-based learning. This research is qualitative research that used observation, documentation, and interviews as the data collection techniques. The study results indicate that the integration of social studies learning had not been maximized due to the lack of school readiness. The teachers and project teams are unfamiliar with project-based learning. Project-based learning is only focused on the produced product or the work without paying attention to the process in each project flow. The driving factor for integrating social studies learning is the principal's ability as the learning leader. The principal can also organize teachers and project teams to integrate social studies learning appropriately and map schools' readiness to carry out project learning. The inhibiting factor in integrating social studies material is the teacher's lack of understanding in integrating social studies learning, so the prioritized themes in this subject cannot be developed optimally.